2010
DOI: 10.1136/jmg.2010.077552
|View full text |Cite
|
Sign up to set email alerts
|

Association between a common mitochondrial DNA D-loop polycytosine variant and alteration of mitochondrial copy number in human peripheral blood cells

Abstract: Our results substantiate a previous suggestion that the mtDNA 16189 variant can cause alteration of mtDNA copy number in human blood cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
72
3
5

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(85 citation statements)
references
References 24 publications
3
72
3
5
Order By: Relevance
“…The DNA levels of the human mitochondrial ND1 (NADH dehydrogenase 1) gene and nuclear 18 S rRNA were determined by real-time PCR quantification. The relative mtDNA content was reflected by the ratio of DNA levels between mitochondrial ND1 and nuclear 18 S rRNA as described previously (26).…”
Section: Methodsmentioning
confidence: 99%
“…The DNA levels of the human mitochondrial ND1 (NADH dehydrogenase 1) gene and nuclear 18 S rRNA were determined by real-time PCR quantification. The relative mtDNA content was reflected by the ratio of DNA levels between mitochondrial ND1 and nuclear 18 S rRNA as described previously (26).…”
Section: Methodsmentioning
confidence: 99%
“…When the T16189C polymorphism is accompanied by a second nucleotide change, which is often the case at np 16192, the poly-C is interrupted again. Liou et al showed that different poly-C variants showed differences in mean mtDNA copy numbers [38]. Subjects with an uninterrupted poly-C had the lowest mtDNA copy number, whereas subjects harboring an interrupted poly-C showed the highest mtDNA copy number.…”
Section: Discussionmentioning
confidence: 99%
“…The C150T transition of mtDNA D-loop was found to cause the change of the mtDNA 151 replication origin in human leukocytes and fibroblasts and associate with the longevity of human being . A variable length of poly-C tract was found to generate from a T-to-C transition at a specific position of mtDNA (np16189 or D-loop np667) and interfere with mtDNA replication, resulting in a series of diseases (Liou et al 2010). The T-to-C transition of mtDNA np16189 was confirmed to be a predisposing genetic factor for the development of insulin resistance which associated with the pathogenesis of diabetes mellitus, stroke, and cardiovascular diseases (Liou et al 2004).…”
Section: Discussionmentioning
confidence: 93%